PENERAPAN STRATEGI PENGUATAN BUDAYA KERJA DALAM MENINGKATKAN KINERJA PEGAWAI DI PDAM TIRTA BENTENG TANGERANG - Fajar Eryanto Septiawan (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
The phenomenon that occurs in regional companies, especially PDAM (Regional Water Supply Company) Tirta Benteng Tangerang, is the number of consumer complaints in recent years both on the Google website and the company's internal data. This study aims to determine the application of strategies to strengthen work culture in improving employee performance at PDAM Tirta Benteng Tangerang. This study uses qualitative methods with data collection techniques in the form of interviews. The results of the study found that the strategies for implementing work culture carried out by PDAM Tirta Benteng Tangerang in improving employee performance were strategies for strengthening work culture, bureaucratic strategies, external strengthening strategies, and culture-based performance improvement strategies.